Pengaruh Earning Per Share, Debt To Equity Ratio dan Return On Equity terhadap Harga Saham pada Perusahaan Kesehatan yang Terdaftar di BEI Periode 2022-2024 - Indah Pratiwi; Nisfu Fhitri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The healthcare sector has become one of the strategic industries attracting investors in the Indonesian capital market. Stock prices are influenced by various financial performance indicators, including Earning Per Share (EPS), Debt to Equity Ratio (DER), and Return On Equity (ROE). This study aims to examine the effect of EPS, DER, and ROE on stock prices of healthcare companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research employed a quantitative approach with an associative research method. The population consisted of 28 healthcare companies, while the sample was determined using purposive sampling, resulting in 11 companies. The study utilized secondary data in the form of company financial statements obtained from the Indonesia Stock Exchange and company websites. The data were analyzed using multiple linear regression with SPSS version 25. Hypothesis testing included classical assumption tests, simultaneous tests (F-test), partial tests (t-test), and coefficient of determination (R²). The results indicate that Earning Per Share (EPS), Debt to Equity Ratio (DER), and Return On Equity (ROE) do not simultaneously have a significant effect on stock prices, suggesting that stock price movements in the healthcare sector are not fully explained by internal financial ratios. Only EPS has a significant partial effect, indicating that investors primarily consider earnings per share in investment decisions, while DER and ROE are not significant. The R² value of 12.1% shows limited explanatory power of the model, with most variations driven by external factors.